Il nazismo ed i crimini contro l’umanità. Psicoanalisi e "diritto naturale" - Fargnoli, Domenico (Il sogno della farfalla, 1996)
Il nazismo ed i crimini contro l’umanità. Psicoanalisi e "diritto naturale"